Entre a sereia e o vigário: discursos sobre Ciência, Tecnologia & Inovação no campo científico brasileiro - Paula, Erico Lopes Pinheiro de (2021)
This study investigates discourses of (not only) scientific associations regarding economic development and innovation. The discourses were delivered through institutional websites and the legislative arena, aiming at hegemony in policies for science, technology, and innovation in Brazil. Our general research problem referred to the consensus defended and the propositions debated in the lower and upper House of Representatives. Our main objective was to reveal the role of academic associations in this process, as well as to map problems detected and solutions prescribed by them. We strategically pointed out aspects of the discourses that have, in their form, the seal of academy (mermaid metaphor) and, in their content, the intransigent defense of an obsolete perspective of state (vicar metaphor). The method is referred to in theories on symbolic capital, scientific field, and economic development, which allowed us to approach historical, social, and political aspects in our explanations. This theory guided us in the criticism to the entities’ main arguments, aiming to expose specific conditions of underdeveloped countries and contradictions inherent to the establishment of public policies for higher education. We exclusively used texts and audios available at the Internet, at the House of Representative’s website, and at the institutional websites of associations (herein referred to as entities). The sample primarily entails what was published from 2011 to 2016 and, additionally, the entities’ textual production between 2016 and 2018. Data were collected remotely, as all repositories used were widely available during the research period. Subsequently, the material was assessed, catalogued, and transcribed when necessary. Analysis was performed through a critical reading of various genres and a subsequent triangulation of data – when comparing the entities’ bibliographical production, institutional debates in Public Hearings at the House of Representatives, and the legislation enacted. Our results show an intense convergence of the entities’ agenda and a decisive influence on the promulgation of the new Legal Framework for Science, Technology, and Innovation. We concluded that the coalition (academic entrepreneurs, public managers, and private investors) perceived the problems that affect knowledge production and industrial activity in contemporary Brazil in a partial and insufficient way – especially when compared with mission-oriented innovation policies.